VALUE ORIENTATION AND MARITAL HARMONY AMONGST MARRIED EMPLOYEES IN MUNICIPAL AREA COUNCIL OF FEDERAL CAPITAL TERRITORY, ABUJA NIGERIA - AYUBA, Iya H.; DAKUP, Dominic; OKECHUKWU, Henrietta; PUR, Hamsatu J. (Journal of Professional Counselling, 2024)
This study investigated the relationship between value orientation and marital harmony amongst married employees in municipal area council of Federal Capital Territory (FCT), Abuja Nigeria. Research questions and hypotheses guided the study. Correlation survey design was adopted for this study. The population of the study comprised married employees in Abuja Municipal Area Council of FCT. The sample of the study consists of 150 participants sampled using purposiverandom sampling technique. A researchers’ made instrument titled; Value Orientation and Marital Satisfaction Scale (VOMSS) was used for collecting data. Validity of the instrument ascertained by experts was 0.78. Reliability was determined using Cronbach Alpha which yielded 0.82. Data were analyzed using Pearson Product Moment Correlation. The results revealed significant relationship between value orientation and marital harmony amongst couples in FCT. Researchers recommended that counsellors should organize marriage seminars periodically to empower couples to imbibe values that promote openness, readiness to change, respect, tolerance, perseverance, forgiveness and love in their marital relationship. Similarly, stakeholders in various cultural and traditional institutions as well as government orientation agencies should embark on vigorous campaigns to reorient the populace on obnoxious social and cultural beliefs that serve as breeding grounds for marital disharmony.